The impact of non-modifiable sociodemographic factors on bladder cancer survival outcomes after radical cystectomy: A systematic review and cumulative analysis of population cohort studies - Yip, Wesley; Chen, Andrew B.; Basin, Michael F.; Cacciamani, Giovanni E.; Bhanvadia, Sumeet K. (Frontiers in Urology, 2022)
Introduction: Sociodemographic factors have been shown to have significant impacts on bladder cancer (BC) outcomes, but there is conflicting data in the literature regarding certain non-modifiable factors. We sought to determine the effect of sociodemographic factors on survival outcomes after radical cystectomy (RC) for BC. Materials and Methods: A systematic review of population-based cohort studies published before March 2020 from Surveillance, Epidemiology, and End Results (SEER) and National Cancer Database (NCDB) was performed per Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines by searching PubMed®, Scopus®, and Web of Science®. All full-text English-language articles assessing the impact of sociodemographic factors on BC survival after RC were obtained. Two investigators (WY, AC) independently screened all articles. Discrepancies were resolved by consensus. All studies reporting survival outcomes after RC based on any of the sociodemographic factors were included, except for systematic reviews, which were excluded. Primary endpoints were overall survival (OS) and disease specific survival (DSS) after RC. Cohort studies reporting Cox proportional hazards or logistic regression analysis were independently screened. Available multivariable hazard ratios (HR) were included in the quantitative analysis. Results: Our search returned 147 studies, of which 14 studies (11 SEER, 3 NCDB) were included for cumulative analysis. Only race and gender were evaluable due to heterogeneity of other factors. Compared to Whites, Blacks have worse OS (HR 0.83;95%CI 0.75,0.92;p<0.01;I2=79%) and DSS (HR 0.83;95%CI 0.69,1.00;p=0.05;I2=69%), Asians have worse OS (HR 0.84;95%CI 0.77,0.92;p<0.01;I2=15%) but not DSS (HR 0.81;95%CI 0.31,2.10;p=0.66), Hispanics have no difference in OS (HR 1.03;95%CI 0.79,1.34;p=0.66;I2=72%) or DSS (HR 2.63;95%CI 0.34,20.34;p=0.35), and Native Americans have no difference in OS (HR 2.16;95%CI 0.80-5.83;p=0.13). Compared to males, females have no difference in OS (HR 1.03;95%CI 0.93,1.15;p=0.53;I2=92%) nor DSS (HR 0.99;95%CI 0.90,1.08;p=0.78;I2=1%). Conclusions: Disparate BC survival outcomes after RC are present, with Blacks having poorer OS and DSS as compared to Whites. Asians have lower OS but not DSS. Survival outcomes do not appear to differentiate by gender. Significant heterogeneity in variable and outcome definitions limited our ability to perform meta-analyses involving other potentially important drivers and sources of disparate outcomes.